Storage of Technical (Porous) Ammonium Nitrate - Erik Nygaard (International Society of Explosives Engineers, 2008)
During the last years, ammonium nitrate has been involved in several accidents worldwide. This have caused increased focus on security and safety issues and resulted in:• Revised Yara standards • Revised international standards for storage and transportation • Stricter regulations from national authorities in many countries.